2022
DOI: 10.1021/acsphotonics.2c00816
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trend in Unconventional Metasurfaces: From Nonlinear, Non-Hermitian to Nonclassical Metasurfaces

Abstract: Metasurfaces, benefiting from the flexibility in engineering the resonance, near-field, symmetry, and scattering properties of individual building blocks, are promising not only for a wide range of practical applications in the classical linear optical regime, but also facilitate research into new unconventional areas. Very recently, we have been witnessing the second quantum revolution in which quantum information processing and computation are becoming a reality. In this review, we will focus on some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 181 publications
0
8
0
Order By: Relevance
“…The diversity of degrees of freedom provided by this system can enable a wealth of applications in solid‐state colors, high‐density optical data storage and encryption. The polarization‐controlled spectral responses demonstrated in this work could be further extended with freeform and unconventional meta‐optics [ 29 ] and the assistance of artificial intelligence. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of degrees of freedom provided by this system can enable a wealth of applications in solid‐state colors, high‐density optical data storage and encryption. The polarization‐controlled spectral responses demonstrated in this work could be further extended with freeform and unconventional meta‐optics [ 29 ] and the assistance of artificial intelligence. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…They are compact and friendly in integration. [5][6][7][8][9][10][11][12] Meta-holograms have been widely developed [13][14][15][16][17][18][19][20][21] under the rising tide of metasurfaces. They can reach high efficiency and provide vivid displays, especially after combining them with quantum correlation imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces are a kind of high-performance platform composed of a subwavelength antenna. They are compact and friendly in integration 5 12 Meta-holograms have been widely developed 13 21 under the rising tide of metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chiral lasing [30] and quantum entanglement. [31,32] To address this challenge, the idea of combining high-Q quasi-BICs resonances with chirality seems promising. To this end, several pioneering studies reported on the creation of chiral quasi-BIC resonances with giant circular dichroism (CD) in dielectric platforms.…”
Section: Introductionmentioning
confidence: 99%